Hubungan Regulasi Emosi dengan Stres Akademik Pada Mahasiswa Prodi Bimbingan dan Konseling Universitas Muslim Nusantara Al Washliyah Medan - Regita Cahyati; Nurul Azmi Saragih; Vinda Chairunnisa; Khairina Ulfa Syaimi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the relationship between emotional regulation and academic stress among students in the Guidance and Counseling study program at Universitas Muslim Nusantara Al Washliyah Medan. The study is grounded in the importance of emotional regulation skills in helping students cope with the various academic demands that can trigger academic stress. Students with effective emotional regulation tend to be better at controlling their emotions, managing pressure, and facing academic challenges adaptively, thereby potentially experiencing lower levels of academic stress. This study employs a quantitative approach using a correlational method. A sample of 33 students was selected using purposive sampling. The instruments used were questionnaires measuring emotional regulation and academic stress, designed based on a Likert scale. The results indicate that the data are normally distributed and the relationship between the two variables is linear. The Pearson Product-Moment correlation test yielded a correlation coefficient (r) of -0.601 with a significance value of 0.000 (p < 0.05). These results demonstrate a significant negative relationship between emotional regulation and academic stress among the students. The coefficient of determination of 36.1% indicates that emotional regulation contributes to academic stress, while the remaining 63.9% is influenced by factors not examined in this study. The findings suggest that the better a student's ability to manage their emotions, the lower the level of academic stress they experience. Therefore, emotional regulation skills should be continuously developed to enable students to better handle academic demands and minimize the occurrence of academic stress